UV-Mediated Photofunctionalization of Indirect Restorative Materials Enhances Bonding to a Resin-Based Luting Agent - Ishikawa, Kyoko; Yamauti, Monica; Tichy, Antonin; Ikeda, Masaomi; Ueno, Takeshi; Wakabayashi, Noriyuki; Thanatvarakorn, Ornnicha; Prasansuttiporn, Taweesak; Klein-Junior, Celso Afonso; Takahashi, Akifumi; Takagaki, Tomohiro; Nakajima, Masatoshi; et al. (BioMed research international, 2021)
PURPOSE: The potential of UV-mediated photofunctionalization to enhance the resin-based luting agent bonding performance to aged materials was investigated. METHODS: Sixty samples of each material were prepared. Yttria-stabilized zirconia (YZr) and Pd-Au alloy (Pd-Au) plates were fabricated and sandblasted. Lithium disilicate glass-ceramic (LDS) was CAD-CAM prepared and ground with #800 SiC paper. Half of the specimens were immersed in machine oil for 24 h to simulate the carbon adsorption. Then, all of the specimens (noncarbon- and carbon-adsorbed) were submitted to UV-mediated photofunctionalization with a 15 W UV-LED (265 nm, 300 mA, 7692 μW/cm2) for 0 (control groups), 5, and 15 min and subjected to contact angle (Ɵ) measurement and bonded using a resin cement (Panavia™ V5, Kuraray Noritake, Japan). The tensile bond strength (TBS) test was performed after 24 h. The Ɵ (°) and TBS (MPa) data were statistically analyzed using two-way ANOVA and Bonferroni correction tests (α = 0.05). RESULTS: In the carbon-adsorbed groups, UV-mediated photofunctionalization for 5 min significantly decreased Ɵ of all materials and increased TBS of YZr, and UV for 15 min significantly increased the TBS of LDS and Pd-Au. In noncarbon-adsorbed groups, UV-photofunctionalization did not significantly change the Ɵ or TBS except YZr specimens UV-photofunctionalized for 15 min. CONCLUSION: UV-mediated photofunctionalization might have removed the adsorbed hydrocarbon molecules from the materials' surfaces and enhanced bond strengths of Panavia™ V5 to YZr, LDS, and Pd-Au. Additionally, UV-mediated photofunctionalization improved the overall TBS of YZr. Further investigation on the optimum conditions of UV photofunctionalization on indirect restorative materials should be conducted.
Keywords: Dental Porcelain; zubní porcelán; vazba zubní; pryskyřičné cementy; Dental Bonding; Yttrium; design s pomocí počítače; Ceramics; Adsorption; zlato; povrchové vlastnosti; lidé; Computer-Aided Design; Ultraviolet Rays; Tensile Strength; Hydrocarbons; zubní slitiny; Zirconium; analýza zatížení zubů; palladium; Materials Testing; keramika; prospektivní studie; Photochemistry; zirkonium; Prospective Studies; testování materiálů; pevnost v tahu; uhlovodíky; Dental Alloys; fotochemie; Dental Stress Analysis; Gold; Carbon; uhlík; Palladium; Surface Properties; Resin Cements; adsorpce; ytrium; ultrafialové záření; Humans